Conceptual Design of Umrah Learning Media Based on Augmented Reality (AR) - Mohammad 'Ulyan; Ni'matu Sholikhah; Khusnin Najwa; Ahmad Khoirurrozikin (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2026)
The background of this research is due to the lack of understanding of prospective Umrah pilgrims, which is a challenge in carrying out the Umrah pilgrimage for first-time pilgrims. The relatively high cost of travel and accommodation makes it important for prospective pilgrims to prepare thoroughly so that their worship is valid and in accordance with Islamic law. Furthermore, technological changes can be an opportunity to develop learning media that remain relevant to current conditions. Currently, Umrah learning is carried out through conventional manasik (rituals) by manually constructing the Kaaba. This study aims to formulate a basic concept for developing Augmented Reality (AR)-based Umrah learning media. This research method uses the DDR (Design and Development Research) method, which is a systematic study of the design, development, and evaluation processes with the aim of establishing an empirical basis for the creation of products and learning tools, as well as new or improved models that govern their development. The novelty in this study contributes to Augmented Reality-based Umrah learning media. The novelty of this research lies in the design of an Augmented Reality-based learning media concept for Umrah rituals, which can interactively depict each series of Umrah rituals in the form of 3D objects on the device, thus providing a more immersive, flexible, and easy-to-understand learning experience compared to conventional learning methods.